QAnon Beliefs, Political Radicalization and Support for January 6th Insurrection: A Gendered Perspective - Moskalenko, Sophia (Terrorism and political violence, 2024)
This study measured political radicalization and support for the January 6th riot alongside a measure of QAnon conspiracy beliefs in an online survey of 429 U.S.-based participants. The study aimed to investigate how conspiracy theories associated with the QAnon movement relate to support for the January 6th Capitol Hill riot and political radicalization, as well as explore the contribution of the Big 5 personality traits. Additionally, the study explored the gender dimension of QAnon-related radicalization. Belief in QAnon conspiracy theories correlated with intentions for radical political action, and with support for the January 6th insurrection. Agreeableness negatively correlated with QAnon beliefs. In our sample, more women reported believing QAnon conspiracy theories, and their average endorsement of QAnon conspiracies was higher than that of men. In women in our study, support for January 6th riot was positively related to Openness to Experiences, and activism and radicalism were positively related to extraversion; these relationships were reversed among men. These gender differences suggest a different psychology underlying QAnon’s appeal for men versus women, and radicalization stemming from beliefs in QAnon conspiracy theories.